PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), PERSISTENSI LABA, TIMELINESS, DAN RISIKO SISTEMATIK TERHADAP EARNINGS RESPONSE COEFFISIENT (ERC): STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wardhana, Reinaldi Wisnu; Achyani, Fatchan (LP2M Universitas Bina Bangsa, 2025)
This study aims to determine the influence of corporate social responsibility, profit persistence, timeliness, and systematic risk on earnings response coeffisient. The population used in this study includes all companies listed on the Indonesia Stock Exchange (IDX) in the form of financial statements. The sampling technique used the purposive sampling method according to the criteria that had been determined and 72 samples were obtained. However, 5 samples were outliers, so that the final total of samples after the outlier was 67 samples that could be used in the study. The data analysis method used is a multiple linear regression analysis model. The results showed that the variables of corporate social responsibility (CSR) and systematic risk had an effect on earning response coefficient (ERC), while profit persistence and timeliness had no effect on earning response coefficient (ERC)